2022
DOI: 10.1061/(asce)gt.1943-5606.0002930
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Liquefaction-Induced Downdrag: Validation against Centrifuge Model Tests

Abstract: Earthquake-induced soil liquefaction can cause soil settlement around piles, resulting in drag load and pile settlement after shaking stops. Estimating the axial load distribution and pile settlement is important for designing and evaluating the performance of axially loaded piles in liquefiable soils. Commonly used neutral plane solution methods model the liquefiable layer as an equivalent consolidating clay layer without considering the sequencing and pattern of excess pore pressure dissipation and soil sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…The writers would like to note that the instrumentation of the 0DPile measuring axial load was sensitive to bending and thus could cause errors resulting in some unusual and unexplainable axial load distribution. Laboratory tests (Sinha et al 2021b) and the subsequent SKS03 centrifuge model test (Sinha 2022;Ziotopoulou et al 2022) also confirmed this anomaly. Moreover, the inclination of 0DPile (vertically by about 1.4°) could have also resulted in bending moments affecting the axial load measurement.…”
Section: Interpretation Of Shaking Test Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The writers would like to note that the instrumentation of the 0DPile measuring axial load was sensitive to bending and thus could cause errors resulting in some unusual and unexplainable axial load distribution. Laboratory tests (Sinha et al 2021b) and the subsequent SKS03 centrifuge model test (Sinha 2022;Ziotopoulou et al 2022) also confirmed this anomaly. Moreover, the inclination of 0DPile (vertically by about 1.4°) could have also resulted in bending moments affecting the axial load measurement.…”
Section: Interpretation Of Shaking Test Resultsmentioning
confidence: 75%
“…The writers realize that, due to instrumentation limitations, an experiment may not provide all data of interest; thus, for a more detailed investigation, follow-on validated numerical simulations are used to extract more insights. Sinha et al (2022) developed a numerical approach (TzQzLiq analysis) for modeling the response of axially loaded piles in liquefiable soils and validated it against these centrifuge test results. Through the numerical work, Sinha et al (2022) described the mechanism of the development of drag load, neutral plane, and axial load distribution in 0DPile and 5DPile.…”
Section: Interpretation Of Shaking Test Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The magnitude of pore pressure increase in the dense layer depends on the relative thicknesses of the layers and drainage boundary conditions. This issue is examined in more detail in Sinha (2022). When the loose sand layer was fully liquefied (between the depths of 5-12 m), the interface skin friction for the 5DPile in the liquefied layer was reduced to zero and, consequently, the drag load vanished [Fig.…”
Section: During Shakingmentioning
confidence: 99%